Sources and Transformations of Dissolved Lignin Phenols and Chromophoric Dissolved Organic Matter in Otsuchi Bay, Japan - Lu, Chia-Jung; Benner, Ronald; Fichot, Cédric G.; Fukuda, Hideki; Yamashita, Youhei; Ogawa, Hiroshi (Frontiers in Marine Science, 2016)
Dissolved lignin phenols and optical properties of dissolved organic matter (DOM) were measured to investigate the sources and transformations of terrigenous DOM (tDOM) in Otsuchi Bay, Japan. Three rivers discharge into the bay, and relatively high values of syringyl:vanillyl phenols (0.73 ± 0.07) and cinnamyl:vanillyl phenols (0.33 ± 0.10) indicated large contributions of non-woody angiosperm tissues to lignin and tDOM. The physical mixing of river and seawater played an important role in controlling the concentrations and distributions of lignin phenols and chromophoric DOM (CDOM) optical properties in the bay. Lignin phenol concentrations and the CDOM absorption coefficient at 350 nm, a(350), were strongly correlated in river and bay waters. Measurements of lignin phenols and CDOM in bay waters indicated a variety of photochemical and biological transformations of tDOM, including oxidation reactions, photobleaching and a decrease in molecular weight. Photodegradation and biodegradation of lignin and CDOM were investigated in decomposition experiments with river water and native microbial assemblages exposed to natural sunlight or kept in the dark. There was a rapid and substantial removal of lignin phenols and CDOM during the first few days in the light treatment, indicating transformations of tDOM and CDOM can occur soon after discharge of buoyant river water into the bay. The removal of lignin phenols was slightly greater in the dark (34%) than in the light (30%) during the remaining 59 days of the incubation. Comparison of the light and dark treatments indicated biodegradation was responsible for 67% of total lignin phenols removal during the 62-day incubation exposed to natural sunlight, indicating biodegradation is a dominant removal process in Otsuchi Bay.